Analisis Pengaruh Diversifikasi Perusahaan terhadap Manajemen Laba - Aryati, Titik; Walansendouw, Yoel Charisma (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
The objective of this research is to examine the effect of corporate diversification on earningsmanagement. Corporate diversification is measured by Herfindahl Index, while earningsmanagement is measured by discretionary current accruals. This research used 53 firms listedin Indonesia Stock Exchange on 2008-2010. The hypotheses in this research are tested by usingmultiple regression analysis. The result of this research shows that corporate diversification doesnot give significant effect to earnings management.